If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4p + 19 = 11 Reorder the terms: 19 + 4p = 11 Solving 19 + 4p = 11 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 4p = 11 + -19 Combine like terms: 19 + -19 = 0 0 + 4p = 11 + -19 4p = 11 + -19 Combine like terms: 11 + -19 = -8 4p = -8 Divide each side by '4'. p = -2 Simplifying p = -2
| 6x-5(x-12)=92 | | x/4-7=-10 | | 70n-15+n=2n-8-40n | | 7-c=16 | | 0.25r+4.75= | | -30+12=18d | | 8r+4= | | 10=11x-23 | | -5(x-3)=10x | | 42-3y=333-y | | 3x+7=12x-1 | | 3[4+4x]=12x+12 | | -7(2x+5)=-5(1+4x) | | -17x-25=19-15x | | 14x+x+x+4+(-6)=14x+x+x+4-6 | | 0=9x+81 | | 7+4x-1=12 | | 3(2x-1)-6x=-4 | | 8(n-2)-3(n-4)=6(n-7)+8 | | 3x-7=3x+13 | | -6(4x-2)=-24x+12 | | 1/4(4q+12)=2+18-3q | | 0.25+4.75=6 | | -12+21=-3 | | 18x+9y=360 | | 4x-11=-23 | | 3(2x-4)=21 | | 2x-4+0.5(2+8x)=0 | | 36-11=5(x-4) | | 33+3y-12=12y-9-4y | | -1y-22-1y=-16 | | 15=-3(n-4) |